Simulasi Koefisien Parameter DAS dalam Membangkitkan Debit Sintesis dengan Metode Nreca (Studi Kasus pada DAS Sekampung Propinsi Lampung) - Andy Eka Saputra; Kelik Istanto; Iskandar Zulkarnain (Jurusan Teknologi Pertanian, 2012)
This study aims to create a simulation of watershed parameters in the coefficient generating discharge data by the method of synthesis of NRECA at watershed Sekampung. The research was conducted at Polytechnic Lampung in August and November 2011. Search the data using charts NRECA created four stages of simulation, of the four simulations have started to show a trend following observations have been made. From the results of the simulation parameters to manufacture-4 is closer to a state of observation and calculation. This is shown by - average number of discharges with the same observation. Visually, the graph is closer to the observation that the model parameters can be used to predict the amount of discharge, especially in watershed areas compatriot Lampung Province. The best simulation on the simulation of the four obtained values of model parameters correlation coefficient Qobs Vs Qsim of 0.27 with the watershed parameters Sinitial: 50, Gwinitial: 50, SNOM: 100, Krech: 0.85, 0.63 K Base and CF: 0.72. included in watershed characteristics that have characteristics of watersheds with high permeable aquifers and discharge the small mainstay. Keywords: NRECA, model parameters, DAS, discharge synthesis